Fotokatalis Titanium Oksida (TiO2) Doping Tembaga (Cu) Menggunakan Metode Sol Gel untuk Fototransformasi Zat Warna Methylene Blue - Anjali, Ghoury Kharisma; Zainul, Rahadian (MASALIQ, 2024)
Methylene blue is a heterocyclic synthetic dye used in the textile industry, but it has a negative impact on water quality and the surrounding environment. This research aims to degrade Methylene blue using a photocatalytic method. The catalyst used for degradation is TiO2 doped with 10% Cu. In this research, the degradation process uses 25 watt Uv light using a reactor. The degradation process was carried out by varying stirring at a speed of 1500 rpm and without stirring at 30, 60, 90 and 120 minutes. The degradation results were measured using a UV-Vis spectrophotometer to see the absorbance before and after degradation, and FTIR to see the shift in compound bonds. The results of this research showed that degradation using stirring had a higher percentage of degradation than without stirring. The maximum degradation percentage obtained in the research was 92.31% with a stirring speed of 1500 rpm for 120 minutes of exposure.